Rapid degradation of oseltamivir phosphate in clinical samples by plasma esterases. - Lindegardh, N; Davies, G; Tran, T; Farrar, J; Singhasivanon, P; Day, N; White, N (2006)
The anti-influenza drug oseltamivir is an ester prodrug activated by hepatic carboxylesterases. Plasma esterases also convert up to 31.8% of the parent compound to the active metabolite after 4 h ex vivo, with wide interindividual variation. This source of error is removed by adding the esterase inhibitor dichlorvos to blood collection tubes.